Interactions of Daphnodorin B and Daphentin with Calf Thymus DNA - Li, Qiang; Yu, Yanying; Cao, Shuwen (Asian Journal of Chemistry, 2011)
The interactions of daphnodorin B and daphentin with calf thymus DNA (ctDNA) were investigated. The binding constants of daphnodorin B and daphentin with ctDNA were obtained by UV spectroscopy. Further, the binding mechanisms on the reaction of the two compounds with ctDNA and effect of ionic strength on the fluorescence property of the system have also been investigated. The results of the assay indicate that daphnodorin B intercalates with ctDNA while daphentin interacts with ctDNA by groove binding. And the binding constants of daphnodorin B and daphentin with ctDNA were 3.261 × 105 and 1.063 × 104 L mol-1, respectively.